PERANCANGAN BUKU POP-UP MUSEUM SANGIRAN SEBAGAI MEDIA PEMBELAJARAN TENTANG PENINGGALAN SEJARAH - Khoirotun, Anisah; Fianto, Achmad Yanu Alif; Riqqoh, Abdullah Khoir (Jurnal ArtNouveau, 2014)
Sangiran Museum is the one of archaeological museum that has a collection of the most complete early human fossils in Java. The museum was founded as a place to learn about the particularly historical relics of ancient human. However, teens are now less keen to visit the museum, because the museum is considered a boring place. So the present teenage knowledge of the history of early man is very limited. Therefore, the design aims to create an alternative media such as pop-up books that are used as a learning media to learn historical heritage. This design uses qualitative research that is by observation, interviews, documentation and literature to obtain data that used to support making the design concept of branding. Data were analyzed using multiple phases, namely data reduction, data display, and conclusion. Through the analysis of data obtained theme design concept is